Correction: The moderating role of sociodemographic and work-related variables in burnout and mental health levels of Mexican medical residents. - Alejandra Del Carmen Dominguez-Espinosa; Sandra Irma Montes de Oca-Mayagoitia; Ana Paola Sáenz-Jiménez; Javier de la Fuente-Zepeda; Lilia Monroy Ramírez de Arellano (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0274322.].